Pengembangan Aplikasi Web untuk Monitoring, Tracking, dan Inventarisasi Peminjaman Laptop pada PT Integrasi Data Nusantara - Sutisna; Tubagus Adhitya Permana; Mahesa Yudha Pratama; Nasrullah Syamil Salahudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
PT Integrasi Data Nusantara (ID-Networkers) is a company that provides training and certification in the field of information technology. In its implementation, the company faces issues related to the management of laptops borrowed by training participants, where there is no organized system to record the borrowing status, resulting in the risk of device loss and reduced training efficiency. To address this, a web application has been developed for monitoring, tracking, and inventorying laptop loans. This application is designed to assist warehouse administrators in recording and tracking device status in real-time, as well as ensuring the timely return of laptops. The methods used in the development of this application include literature review, system requirement analysis, and system testing by distributing questionnaires to application users. The testing results show that this application can enhance the efficiency of device management, minimize the risk of laptop loss, and support the smooth running of training programs. With this application, it is expected that PT Integrasi Data Nusantara can better manage its devices, improve training efficiency, and ensure optimal device availability for training participants.